The effect of Arginine, Lysine and Histidine in the myosin secondary structure by circular dichroism and Raman spectroscopy - Tong Shi; Li Yuan; Jianlou Mu; Ruichang Gao (CyTA - Journal of Food, 2019)
Amino acids containing L-Arginine (Arg), L-Lysine (Lys) and L-Histidine (His) are recognized to increase the solubility of myosin at low ionic strength, but there is a difference in the researchers’ views on their effects on the secondary structure of myosin. To elucidate which method is relatively appropriate for the determination of secondary structures of myosin added with Arg, Lys or His, Circular dichroism (CD) spectra and Raman spectroscopy were carried out respectively. Raman spectroscopy was more suitable than CD method for determination of the secondary structures of myosin added with His, while CD spectra was more accurate for the myosin samples added with Lys and the adequate concentration of Lys should be under 10 mM. Both CD and Raman methods could be applied to myosin added with Arg, however, the latter was recommended and the adequate additive content of Arg in CD method should be less than 10 mM.